Atomic Absorption Spectrophotometric Method for Magnesium and Iron Determination in Goat Milk Powder - Kusumaningtyas, H.; Febiana, H.; Septiani, L. (Indonesian Journal of Chemistry and Environment, 2018)
This research aims to determine the levels of magnesium and iron in goat milk powder. The method of this research was atomic absorption spectrophotometry. The research subject is goat milk powder while the research object is the amount of magnesium and iron in goat milk powder. Before analyzing, the first step is removing organic substances in the sample that could interfere the analysis by dissolved it in concentrated nitric acid and heated. Based on the measurement using atomic absorption spectrophotometry method, absorbance and concentration of magnesium and iron in the sample were obtained. The analysis showed that the levels of magnesium and iron in the sample were 0.00317 mg/g and 0.02177 mg/g.